A prospective randomized, double blind, placebo-controlled trial of a single dose of surfactant as rescue therapy for infants less than 1000grams who are not ventilated - Savva, Kleopatra (My University, 2014)
To test if a single dose of artificial surfactant given as rescue therapy to extremely low birth weight ( ELBW) infants (i.e. those with birth weight <1000g) with hyaline membrane disease who are not ventilated, will improve their survival.